The newsvendor model with non-zero reference point based on cumulative prospect theory. (November 2017) - Li, Shou-Rong; Zhang, Ren-Qian; Fang, Wei-Guo
Highlights: The NV model with non-zero reference point under cumulative prospect theory (CPT). Develop the first-order conditions of the NV model with non-zero reference point. The proposed NV model partially explains the " pull-to-center " effect. Abstract: This paper formulates the newsvendor model with a non-zero reference point based on cumulative prospect theory (CPT-based newsvendor model), evaluating the prospect by a piecewise-linear value function ( Model PL ). We prove the concavity of the objective function, and therefore, the model is solved by the first-order optimality condition. As a comparison, we further present the newsvendor model based on a piecewise-exponential value function ( Model PE ), where the utility curvatures are considered. The results show that for a low-profit item, only Model PE can explain the " pull to center " effect that was found by Schweitzer and Cachon (2000), if the reference point is high enough. However, for a high-profit item, both models successfully predict the newsvendor's behavior if the newsvendor conceives a non-zero reference point. Thus, prospect theory (PT) should not be excluded as a potential explanation for the " pull to center " effect of the newsvendor's decision.